2023
DOI: 10.7150/ijbs.78535
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Super-enhancers as Therapeutic Targets in The Digestive System Tumors

Abstract: Digestive system tumors include malignancies of the stomach, pancreas, colon, rectum, and the esophagus, and are associated with high morbidity and mortality. Aberrant epigenetic modifications play a vital role in the progression of digestive system tumors. The aberrant transcription of key oncogenes is driven by super-enhancers (SEs), which are characterized by large clusters of enhancers with significantly high density of transcription factors, cofactors, and epigenetic modulatory proteins. The SEs consist o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 139 publications
0
4
0
Order By: Relevance
“…As we discussed above, SEs and regulated genes play important roles in the biological process of cancer cells, and therapy targeting SEs is a promising cancer treatment strategy. Recent research focuses on developing small molecule inhibitors targeting SE components, especially BRD4 and CDK7 inhibitors (Xiang-Ping Li et al, 2023). Pre-clinical studies and undergoing clinical trials showed significant antitumor efficacy of these inhibitors.…”
Section: Research Frontiers and Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we discussed above, SEs and regulated genes play important roles in the biological process of cancer cells, and therapy targeting SEs is a promising cancer treatment strategy. Recent research focuses on developing small molecule inhibitors targeting SE components, especially BRD4 and CDK7 inhibitors (Xiang-Ping Li et al, 2023). Pre-clinical studies and undergoing clinical trials showed significant antitumor efficacy of these inhibitors.…”
Section: Research Frontiers and Prospectsmentioning
confidence: 99%
“…Pre-clinical studies and undergoing clinical trials showed significant antitumor efficacy of these inhibitors. However, limited clinical applications of inhibitors are available because of significant toxicity and adverse events (Xiang-Ping Li et al, 2023). It has been demonstrated in a study that the BRD4/LSD1/NuRD complex is destroyed by the BRD4 inhibitor JQ1 when used for a long period, leading to resistance to JQ1 and a broad spectrum of antitumor compounds (Liu et al, 2022).…”
Section: Research Frontiers and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, many lncRNAs have been identified as novel biomarkers for immunotherapy [ 12 , 13 ]. Super-enhancer-related genes are closely related with many tumor characteristics such as immune response [ 14 ]. Recently, super-enhancer-related lncRNAs (SE-lncRNAs) are emerging as new biomarkers for predicting immunotherapy efficacy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%